Pengaruh Growth Mindset terhadap Grit Akademik pada Mahasiswa Pendidikan Akuntansi Universitas Sebelas Maret - Hanafi, Khalila Albar; Ivada, Elvia (PT Wahana Global Education, 2025)
This study aimed to reveal the influence of growth mindset on academic grit of Accounting Education students at Sebelas Maret University. This study used a quantitative approach which the researcher conducted a survey. The population in this study was the 4th and 6th semester Accounting Education students at Sebelas Maret University. The sampling used a non-probability sampling technique with purposive sampling type, with a total sample of 120 students. The data collection technique used conducted by the researcher is a questionnaire. The instrument validation technique in this research used content validity and construct validity which included validity and reliability tests. The data analysis technique used descriptive analysis and simple regression, partial statistical test (t), and coefficient of determination analysis. The prerequisite tests of analysis in this research used normality test, linearity test, and heteroscedasticity test. The results of this research showed that growth mindset significantly affected the academic grit of Accounting Education students at Sebelas Maret University with a significance value of <0.001 less than 0.005. The regression function model equation obtained from this research was Y = 7.590 + 0.798X.